Strengthening Dewan Kehormatan Penyelenggara Pemilu RI Institutions in the Indonesian Constitutional System - Akbar, Kurniawan; Suartini, Suartini; Suparji, Suparji (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
DKPP RI to align its secretariat with the KPU RI and Bawaslu RI. Through several stages, namely first stabilizing human resources or employees, at least stabilizing staffing needs. This research uses a normative juridical method that examines the law in its position as a norm (das sollen), a statutory approach and a conceptual approach. The results of this research improve the institution of DKPP RI so that its secretariat is on par with the KPU RI and Bawaslu RI. Through several stages, namely first stabilizing staffing needs. As well as fulfilling the budget allocation at least in accordance with the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 67 of 2020 concerning the Strategic Plan of the Ministry of Home Affairs for 2020-2024. Furthermore, after there is stability in staffing and the budget, you can then propose to the DPR RI or the Government to revise the law on elections or make changes to the election law to strengthen the institution of the DKPP RI, namely inserting an article regarding the DKPP Secretariat General as a state civil servant with the position middle school seniors who are appointed and dismissed by the President on the recommendation of the DKPP.